ANALYTICAL REVIEW OF THE CURRENT STATE OF DEVELOPMENT IN THE DESIGN OF ADAPTIVE REHABILITATION GARMENTS - KULESHOVA, SVITLANA; LUSCHEVSKA, OLENA; LEBEDINSKA, OKSANA; SLOBODENIUK, OLGA; KOVALSKA, DARIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article is devoted to an analytical review of the current state of development in the design of adaptive rehabilitation garments of light industry to improve the process of psychophysiological adaptation of people (military and civilians) with traumatic limb injuries. The need to design adaptive clothing for people with lost limbs has been determined, with the aim of increasing a person's independence, creating and maintaining his physical and psychological comfort, as well as ensuring his successful rehabilitation. On the basis of theoretical studies of existing varieties of adaptive products, the most rational structural and technological solutions of the constituent elements of adaptive rehabilitation shoulder and lumbar products were systematized and an information database was formed for the purpose of their informed choice for people (military and civilians) with traumatic limb injuries. Based on research in the field of harmonization of color relationships, taking into account the emotional and psychophysiological impact of color on consumers with traumatic limb injuries, a database and recommendations for the use of harmonious color combinations in adaptive rehabilitation clothing at the hospital and post-hospital stages have been developed. A series of sketches of new models of adaptive shoulder and waist products in the Sport-casual style for consumers with traumatic limb injuries for everyday use, taking into account the needs of aesthetics, ergonomics and socialization, are proposed. Further research is aimed at the production of experimental samples of adaptive products according to the provided sketches in the conditions of the Ukrainian brand ARTY Sport.
Keywords: adaptive rehabilitation garments; traumatic limb injury; psychophysiological adaptation; functional and constructive elements